KAJIAN SEMIOTIKA ROLAND BARTHES TENTANG AZAB KAUM SODOM - Nurhasanah, Nurhasanah (Hadharah: Jurnal Keislaman dan Peradaban, 2023)
The verses that talk about the doom of the sodomites at the time of the Prophet Luth As in the Qur'an. However, the verses are not written textually or literally with the word "doom", there is only a gesture of some kind of sign or symbol. Meanwhile, the diversity of interpretive literature is developing today, that the text of the Qur'an is a sign system in the linguistic-semiotic sense. Therefore, it is important to reveal the meaning hinted at in the form of symbols or signs in these verses and their relationship to doom. One approach that can be used in the study of the Qur'an theoretically interpretively in the linguistic frame is the semiotic approach, to reveal new meanings that are deeper beyond the basic meaning of the doom by using Roland Barthes's theory of semiotics, namely semiotics denotation, connotations and myths. This research uses a type of literature research, for a research approach using a descriptive analytical approach. The primary source is the Qur'an al-Karim and the secondary source is the books of interpretation, books, journals and other supporting books. The results of research obtained from Roland Barthes's semiotic approach to the doom of the sodomites during the time of the Prophet Luth As in the Qur'an, including the meaning of the denotation and connotation of the stone rain on the Prophet Luth AS is a symbol of doom. The mythical meaning of stone rain is a symbol of doom for the one who committed the most heinous deed on the U.S. Prophet Luth.